Levulinic Acid-Inducible and Tunable Gene Expression System for Methylorubrum extorquens - Sathesh-Prabu, Chandran; Ryu, Young Shin; Lee, Sung Kuk (Frontiers in Bioengineering and Biotechnology, 2021)
Methylorubrum extorquens AM1 is an efficient platform strain possessing biotechnological potential in formate- and methanol-based single carbon (C1) bioeconomy. Constitutive expression or costly chemical-inducible expression systems are not always desirable. Here, several glucose-, xylose-, and levulinic acid (LA)-inducible promoter systems were assessed for the induction of green fluorescent protein (GFP) as a reporter protein. Among them, the LA-inducible gene expression system (HpdR/PhpdH) showed a strong expression of GFP (51-fold) compared to the control. The system was induced even at low concentrations of LA (0.1 mM). The fluorescence intensity increased with increasing concentrations of LA up to 20 mM. The system was tunable and tightly controlled with meager basal expression. The maximum GFP yield obtained using the system was 42 mg/g biomass, representing 10% of the total protein content. The efficiency of the proposed system was nearly equivalent (90%–100%) to that of the widely used strong promoters such as PmxaF and PL/O4. The HpdR/PhpdH system worked equally efficiently in five different strains of M. extorquens. LA is a low-cost, renewable, and sustainable platform chemical that can be used to generate a wide range of products. Hence, the reported system in potent strains of M. extorquens is highly beneficial in the C1-biorefinery industry to produce value-added products and bulk chemicals.